The “power” of value-added thinking: Exploring the implementation of high-stakes teacher accountability policies in Rio de Janeiro - Straubhaar, Rolf (Education Policy Analysis Archives, 2017)
The purpose of this article is to ethnographically document the market-based ideological assumptions of Rio de Janeiro’s educational policymakers, and the ways in which those assumptions have informed these policymakers’ decision to implement value-added modeling-based teacher evaluation policies. Drawing on the anthropological literature on meaning making (Anderson-Levitt, 2012), the focus of this study is on the common understandings and ideological assumptions regarding “good” teacher education practice that undergird the policymaking decisions of Rio de Janeiro’s public education policymakers. On the basis of ethnographic interviews, I argue that the then-current Secretariat of Education in Rio was run primarily by people whose backgrounds in business and administration heavily influenced their ideological assumptions about good educational management. I further explore the ways in which Rio’s implementation of value-added modeling and high-stakes accountability-based teacher evaluation mechanisms reflects these latent ideological trends.